Light exposure during late night attenuates the risk of scopolamine-induced Alzheimer disease in aged rats. Issue 1 (1st January 2020) - Abdel-Rahman, Mona; Abdel-Kader, Seham; El-Masry, Heba; El-Hennamy, Rehab E.
ABSTRACT: Decreased light input to the suprachiasmatic nuclei (SCN) is believed to cause alterations of the circadian rhythm. Alzheimer disease (AD) is commonly associated with disturbances in behavior and sleep patterns which is caused by circadian rhythm abnormalities. The present study aimed to investigate the role of light exposure during the night in the re-entrainment of the circadian rhythm in aged rats. Besides, examining the possibility of using light pulse during late night to decrease the risk of Alzheimer disease. Levels of melatonin, acetylcholine (ACh), serotonin (5-HT), and norepinephrine (NE) were measured in four groups of aged rats (control group; light pulse group; scopolamine group, light pulse and scopolamine group). Aged rats exposed to light pulse exhibited a phase shift in the circadian rhythm of neurotransmitters and melatonin. 5-HT levels in the tested brain areas were highly elevated while serum melatonin level was decreased. In most time intervals scopolamine caused a decrease in neurotransmitters and melatonin levels. Exposure to light pulse with scopolamine injection caused an elevation of ACh and 5-HT. In conclusion: light exposure during late-night upsurge serotonin secretion and reduce melatonin levels. A light pulse may exert a protective effect on the progression of AD through enhancement of the neuronal pathway as well as the circadian system via the serotonergic system.